1994
DOI: 10.1016/1044-0305(94)85029-1
|View full text |Cite
|
Sign up to set email alerts
|

On the stabilization of carbanions by adjacent phenyl, cyano, methoxy-carbonyl, and nitro groups in the gas phase

Abstract: Institute of Mass Spectrometry, University of Amsterdam, Amsterdam, The Netherlands By using the method of Fourier transform ion cyclotron resonance mass spectrometry, substituent stabilization energies of homologous series of cycloalkyl carbanions, Ξ-c-CnH2n-2 (n = 3, 4, 5, 6, 7) with π-accepting substituents (Ξ = Ph, CN, COOMe, NO2) have been determined experimentally in the gas phase as the difference between the proton affinity of the substituted and corresponding unsubstituted (Ξ = H) cycloalkyl carbanion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…The ratio of the abundances of the (CH 3 ) 2 RSiO − and (CH 3 ) 3 SiO − ions then reflect the acidity difference between methane and the alkane RH. The proton affinities measured for alkyl and cycloalkyl anions in my group by use of the desilylation method and the home‐built FT‐ICR instrument agreed very well with those obtained by use of the FA‐SIFT method (Peerboom et al, 1992) and have been extended to cycloalkyl anions with various adjacent π‐accepting substituents, the results being analyzed in terms of polarizability, field/inductive, and resonance effects (Peerboom, de Koning, & Nibbering, 1994).…”
Section: The Years Of Fourier Transform Ion Cyclotron Resonance supporting
confidence: 56%
“…The ratio of the abundances of the (CH 3 ) 2 RSiO − and (CH 3 ) 3 SiO − ions then reflect the acidity difference between methane and the alkane RH. The proton affinities measured for alkyl and cycloalkyl anions in my group by use of the desilylation method and the home‐built FT‐ICR instrument agreed very well with those obtained by use of the FA‐SIFT method (Peerboom et al, 1992) and have been extended to cycloalkyl anions with various adjacent π‐accepting substituents, the results being analyzed in terms of polarizability, field/inductive, and resonance effects (Peerboom, de Koning, & Nibbering, 1994).…”
Section: The Years Of Fourier Transform Ion Cyclotron Resonance supporting
confidence: 56%
“…Bimolecular reactions of nitromethane, nitroethane, 2nitropropane and nitrocyclopropane [M -H] anions were investigated with the gas-phase triatomic molecules, extending our early study 19 on deprotonated nitromethane. In addition to the rearranged products formed in the ICR studies (from deprotonated nitromethane 18 and nitrocyclopropane anions 4,5 ), we observed formation of ion-neutral adducts [RNO 2 •X]…”
Section: Reactivities With Co 2 Cs 2 and Somentioning
confidence: 89%
“…3 With the ground state multiplicity problem resolved theoretically, the gas-phase acidity of a-substituted cyclic and acyclic alkanes continues to be a subject of extensive study. [4][5][6] In general, acidity is the result of trade-off between inductive, resonance, polarizability and lone-pair electron repulsion effects and is a measure of stabilization for the deprotonated carbanions. The most acidic hydrogen in nitroalkanes is the one on the a-carbon because of the contribution of the inductive effect of the nitro group on the neutral 1 and the resonance structures 2 and 3 which stabilize the anion formed by deprotonation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations